Austerity and financial governance: a UK case study of the National Health Service. Issue 3 (8th April 2014) - Prowle, Malcolm; Harradine, Don
Abstract : Purpose: – This research concerns the issue of financial governance within the UK NHS and aims to assess the effectiveness of existing financial governance arrangements in the main providers of health services in the UK. Also considered is the importance of good financial governance in a time of financial austerity. Design/methodology/approach: – The primary research for this project was based on the use of a questionnaire to all finance directors in NHSTs in England supported by semi-structured interviews with: finance directors, non-executive directors, executive directors and senior finance staff. Findings: – Among the main findings of the study were: certain financial management systems were not prioritised in line with what is seen as good practice; existing financial management systems were not always seen as adequate for the achievement of good financial governance; there was sometimes a lack of understanding of financial issues by non-executive directors; and the complexity of the NHS funding process often resulted in opaqueness of the financial risks. Research limitations/implications: – The research is limited by the relatively small coverage of NHS trusts but this has been compensated for by a series of in-depth interviews with key stakeholders in the governance process. Practical implications: – Weaknesses in financial governance could result in further scandals which result in loss of life and poor patient care. Originality/value: – There are many papers on the issue of governance in the public sector in general and the NHS in particular. However, there is little published on the issue of financial governance in the NHS. Also of great value is the emphasis on strengthening financial governance in an era of austerity